2021
DOI: 10.1126/sciadv.abf0689
|View full text |Cite
|
Sign up to set email alerts
|

Electric field–catalyzed single-molecule Diels-Alder reaction dynamics

Abstract: Precise time trajectories and detailed reaction pathways of the Diels-Alder reaction were directly observed using accurate single-molecule detection on an in situ label-free single-molecule electrical detection platform. This study demonstrates the well-accepted concerted mechanism and clarifies the role of charge transfer complexes with endo or exo configurations on the reaction path. An unprecedented stepwise pathway was verified at high temperatures in a high-voltage electric field. Experiments and theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 44 publications
2
83
0
Order By: Relevance
“…Instead, we allow the recalculation of the MEP at each step in the global optimization, yielding far more effective and certainly more transferable embeddings. With this strategy, we could confirm external electric field effects on a Diels-Alder reaction that not only lead to strong catalysis, but also to mechanistic changes from a concerted pathway to a zwitterionic, step-wise one, as predicted earlier [11][12][13] and confirmed by different experimental single-molecule techniques [14,15]. Although the MEP recalculation dramatically improves the GOCAT approach, it also highlights one of its downsides: The complex electric fields generated by the point charges are often wildly inhomogeneous and thus become hard to cast into chemical counter-parts.…”
Section: Introductionsupporting
confidence: 70%
“…Instead, we allow the recalculation of the MEP at each step in the global optimization, yielding far more effective and certainly more transferable embeddings. With this strategy, we could confirm external electric field effects on a Diels-Alder reaction that not only lead to strong catalysis, but also to mechanistic changes from a concerted pathway to a zwitterionic, step-wise one, as predicted earlier [11][12][13] and confirmed by different experimental single-molecule techniques [14,15]. Although the MEP recalculation dramatically improves the GOCAT approach, it also highlights one of its downsides: The complex electric fields generated by the point charges are often wildly inhomogeneous and thus become hard to cast into chemical counter-parts.…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, it is reported that chemical reactions can occur in the molecule junctions. [7][8][9][10][11][12][13] Thus, single-molecule junction is an ideal platform to obtain the real-time information of chemical reactions. For example, Guo integrated a single molecule Pd catalyst into GMG-SMJ and achieved the real-time and full description of Suzuki-Miyaura cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66] To make robust devices of atomic dimensions, structural regularity and stability is important, and hence covalent bonding of molecules to silicon offers new technology directions; related covalent-bonding applications involving, e.g., graphene point contacts are also of modern interest. [67][68][69] To date, two types of silicon  molecule  silicon junctions have been prepared using scanning-tunnelling microscopy (STM) technology: "blinking" junctions, formed by holding a silicon STM tip fixed above a SAM of the molecule pre-prepared on a Si(111)-H substrate, and "break-junction" (STMBJ) junctions formed by crashing a silicon tip into a silicon substrate and then withdrawing the tip. Figure 1 illustrates the two approaches.…”
Section: Introductionmentioning
confidence: 99%